English language speaking self-efficacy of students in Univerisiti Teknologi Mara (UiTM) Seremban 3 / Abdul Rahman Arif Azhari and Nuratikah Abdul Razak - Arif Azhari, Abdul Rahman; Abdul Razak, Nuratikah (2019)
English Language has become extra important in Malaysia as employers prefer employees to be more proficient in the English Language command. However, studies have shown that students are not able to speak confidently in English. This study was conducted using a self-administered questionnaire that consists of 32-itemed. The questionnaire was disseminated to 255 Diploma undergraduates taking the Integrated Language Skills III in UiTM Seremban 3. The result showed FSKM (M=3.697) had highest average total mean score for speaking self-efficacy. There was a significant difference in the self-efficacy between the behaviour of the students (p-value < 0. 05). It is indicated that the students with low efficacy score do not speak English at home. Based on the Multiple Linear Regression (MLR), there were seven factors that affected the student's performance which are FSPPP, FSKM, Central, Sabah, Others, number of siblings, CGPA and Speak English at home. The highest contributing factor was CGPA (/3 = 2.400). The implication of these findings were discussed with respect to improve self-efficacy among students to speak English as well as important aspects that influence them.